2021
DOI: 10.3389/fonc.2021.683256
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA SLCO4A1-AS1 Accelerates Growth and Metastasis of Gastric Cancer via Regulation of the miR-149/XIAP Axis

Abstract: ObjectiveRecently, long noncoding RNA SLCO4A1 antisense RNA 1 (SLCO4A1-AS1) has been shown to act as an oncogene in several cancer types; however, its role in gastric cancer (GC) and its underlying molecular mechanisms are yet to be elucidated.MethodsUsing the ENCORI database, we identified SLCO4A1-AS1, miR-149-5p (miR-149), and the X-linked inhibitor of apoptosis (XIAP) whose expressions were obviously changed in GC samples, and analyzed the correlation between their expressions in GC samples. Moreover, we ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…As a study reported, several lncRNAs play an essential part in the tumor occurrence and development of different cancers [47]. For example, Fang et al [48] found that lncRNA SLCO4A1-AS1 was highly upregulated in GC and accelerates growth and metastasis of GC. Furthermore, they conclude that SLCO4A1-AS1 is an important oncogenic lncRNA in GC, and SLCO4A1-AS1 is a potential novel therapeutic target for GC.…”
Section: Discussionmentioning
confidence: 99%
“…As a study reported, several lncRNAs play an essential part in the tumor occurrence and development of different cancers [47]. For example, Fang et al [48] found that lncRNA SLCO4A1-AS1 was highly upregulated in GC and accelerates growth and metastasis of GC. Furthermore, they conclude that SLCO4A1-AS1 is an important oncogenic lncRNA in GC, and SLCO4A1-AS1 is a potential novel therapeutic target for GC.…”
Section: Discussionmentioning
confidence: 99%
“… 25 LncRNA SLCO4A1-AS1 accelerates metastasis of gastric cancer through modulating the miR-149/XIAP axis. 26 RNF144A-AS1 promotes metastasis in gastric cancer by targeting the miR-30c-2-3p/LOX axis. 27 On the other hand, lncRNAs could directly compete with miRNAs to bind with target mRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Further, miR-149-5p was downregulated in the ISO-induced mouse hearts. Previous research has shown that the dysregulation of miR-149-5p is closely associated with malignant tumor progression, metastasis, and chemoresistance in gastric cancer (31)(32)(33), papillary thyroid cancer (34), colorectal cancer (35)(36)(37), and breast cancer (38). Additionally, miR-149-5p is also involved in the pathogenesis of inflammationassociated diseases, such as the PM 2.5 -induced inflammatory response (39), rheumatoid arthritis (40), and chronic obstructive pulmonary disease (41).…”
Section: Discussionmentioning
confidence: 99%